Humean moral pluralism - Gill, Michael B. (Oxford University Press, 2014)
Michael B. Gill offers a new account of Humean moral pluralism: the view that there are different moral reasons for action, which are based on human sentiments. He explores its historical origins, and argues that it offers the most compelling view of our moral experience. Together, pluralism and Humeanism make a philosophically powerful couple
Keywords: Hume, David / 1711-1776; Hume, David -- 1711-1776; Pluralism; Ethics; Conduct of life; Pluralismus; Moral; Ethischer Konflikt